KEEFEKTIFAN PERAN MAHASISWA KKN UNISDA MELALUI PENINGKATAN LITERASI KARAKTERISTIK BUDAYA, PENDIDIKAN, DAN STABILISASI SISTEM INFORMASI AKUNTANSI DI KOPERASI THAILAND - Novi Darmayanti; Mohammad Ali Wafa; Annisa' Carina (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
ABSTRACTThis research aims to evaluate the effectiveness of the role of Darul Ulum Lamongan Islamic University (UNISDA) students in increasing understanding of cultural character, contribution to the field of education, as well as their role in stabilizing cooperatives through the International KKN program in Thailand. The research method used is qualitative with a descriptive approach. The research results show that UNISDA students are able to adapt and understand local culture, make a significant contribution to improving the quality of education, and play an active role in stabilizing cooperatives in target areas.Keywords: Students, International KKN, Culture, Education, Thailand